Influences on rPPG-Based Spatial Blood Perfusion Maps - Kobel Svenja Nicola; Wuerich Carolin; Ernst Anna Lotta; Fusshoeller Eva; Grueter Jan Niclas; Haendler Jakob; Wiede Christian; Seidl Karsten (Current Directions in Biomedical Engineering, 2024)
Recent studies show the feasibility of using local remote photoplethysmography (rPPG) for non-contact blood perfusion assessment by creating spatial pulsatile blood perfusion maps. While global rPPG has been widely studied for its robustness, e.g. for non-contact measurement of heart rate, local analyses pose greater challenges in terms of noise suppression and thus reliability. In this paper, the effect of temperature and illumination changes on signal-to-noise ratio (SNR) perfusion maps is analysed. The results show the importance of consistent temperature and controlled illumination for improving SNR and ensuring reliable blood perfusion measurements using rPPG. This emphasises the need for standardised external conditions for accurate interpretation of the results and medical applicability.